Regional Economic Outlook, October 2016, Middle East and Central Asia. (Regional Economic Outlook, 2016)
This issue focuses on the ongoing adjustment to cheaper oil and subdued economic activity for oil-producing countries, as well as the weak and fragile recovery in the Caucasus and Central Asia region. It also discusses global spillovers from China's rebalancing and the growth of fiscal deficits.